Concurrent Risperidone Administration Attenuates the Development of Locomotor Sensitization Following Sub-Chronic Phencyclidine in Rats - McKibben, C. E.; Reynolds, G. P.; Jenkins, T. A. (Pharmacopsychiatry, 2016)
Introduction: In schizophrenia early treatment may prevent disorder onset, or at least minimize its impact, suggesting possible neuroprotective properties of antipsychotics. The present study investigates the effects of chronic treatment with the atypical antipsychotic, risperidone, on locomotor sensitization in the subchronic phencyclidine-treated rat.Methods: Rats were treated with phencyclidine sub-chronically (2 mg/kg bi-daily for one week followed by a one-week wash-out period) or vehicle. Half of the phencyclidine group was concurrently treated with risperidone (0.5 mg/kg IP) twice daily for 15 days, beginning 3 days before the start of phencyclidine administration. 6 weeks after treatment all rats were injected with a phencyclidine-challenge (3.2 mg/kg) and immediately after their locomotor activity measured for 20 min.Results: Co-administration of risperidone at the time of phencyclidine administration significantly reduced the phencyclidine-challenge locomotor effect administered 6 weeks later.Discussion: These results demonstrate that concurrent risperidone is neuroprotective, and clearly suggests its functionality can be translated to a clinical setting for treating the so-called prodrome.
Keywords: animal models; schizophrenia; risperidone (risperdal)